Management of skeletal Class III with facial asymmetry using skeletal anchorage: 4-year follow-up - Tulika Tripathi; Shilpa Kalra; Priyank Rai
ABSTRACT Introduction: Skeletal Class III malocclusion with asymmetry is one of the most difficult problems to correct in orthodontics. A functional shift of the mandible in growing patients may occur accompanying a Class III, due to constricted maxillary arch and occlusal interferences. Studies have indicated that posterior unilateral crossbite develops early and has a low rate of spontaneous correction. It may further lead to development of mandibular and facial asymmetry by growth and displacement of mandible if left untreated in growing patients. Objective: This article reports the clinical case of a thirteen-year-old female patient in CVMI transition stage that had maxillary hypoplasia with a developing facial asymmetry. Results: The case was successfully managed with bone-anchored facemask therapy and with elimination of occlusal interferences with guided occlusion. Reverse twin block in the retention phase maintained the results achieved. Conclusion: A four-year follow-up evaluation revealed successful maintenance of the treatment results.